Detailed crustal deformation in the Ailaoshan Orogenic Belt revealed by receiver functions from a dense array - Wu, Chenglong; Xu, Tao; Bai, Zhiming (Frontiers in Earth Science, 2023)
The Ailaoshan Orogenic Belt (AOB), located at the southeastern boundary of the Tibetan Plateau, is an ideal place for investigating the mechanisms of lateral growth of Tibet. Using the data recorded by a dense seismic array across the Ailaoshan belt, we investigate the detailed lateral variations of crustal anisotropy on the basis of Pms phase of receiver functions. Remarkable crustal anisotropy is observed throughout this study region with a mean delay time of 0.33 ± 0.19 s, indicating the anisotropy primarily originates in the middle-lower crust. The fast directions beneath the Ailaoshan-Red River shear zone (ARRSZ) as well as its western low-grade metamorphic unit generally align with the NW-SE strike of ARRSZ, indicating the anisotropy is mostly resulted from the strike-slip motion along ARRSZ. The weak anisotropy in the South China Block (SCB) argues that the block is relatively stable, with limited internal deformation. Meanwhile, the anisotropy beneath the western boundary of the SCB is strong, and the N-S oriented fast direction is influenced by both the crustal stress and Xiaojiang Fault. Combining the high Vp/Vs and significant lateral variations of crustal anisotropy parameters, we suggest that the strike-slip motion along the ARRSZ induces the partial melting and pronounced anisotropy in the middle-lower crust of AOB, without the presence of crustal flow. The differences between crustal and mantle anisotropy indicate crust-mantle decoupling deformation of the AOB, supporting the block extrusion model occurring only in the crustal scale as the primary deformation pattern.